Insect predator of spodoptera frugiperda J. E. Smith in Sleman and Gunungkidul regency, Indonesia - Putra, Ichsan Luqmana Indra; Prakusya, Novia Saphira; Yuliasari, Defi (International Research Journal of Insect Sciences, 2023)
This research was conducted to identify and found the abundance of predatory insect species of S. frugiperda in Sleman and Gunungkidul Regencies, Yogyakarta Province, Indonesia. This research was conducted in June 2021 - March 2022 on corn plantations in Sleman and Gunungkidul Regencies. Determination of the sampling location was determined by stratified random sampling. Corn land used in sampling was determined by purposive. Insect predator caught by using sweeping net and hand picking. The results showed that there are 3 orders, 8 families, and 16 species of insect predators. 3 orders of the insect predators that found in the Sleman and Gunungkidul Regencies were Coleoptera, Hymenoptera, and Hemiptera. Insect predator families that found in Sleman dan Guungkidul Regencies were Coccinellidae, Carabidae, Staphylinidae, Formicidae, Vespidae, Pentatomidae and Reduviidae. Insect predators species that was most commonly found was Menochilus sexmaculatus with 467 individuals and the least was Sycanus sp. with 1 individual. The conclusion of this study is that there were 16 species of predators from S. frugiperda in Sleman and Gunungkidul Regencies. Practical implications of this research were the insect predators that found in Sleman and Gunungkidul Regencies can be used to maintain the population of Spodoptera frugiperda in two regencies.